Pengaruh Internal Locus Of Control, Pemberian Punishment Dan Gaya Belajar Visual Terhadap Prestasi Belajar Mahasiswa STKIP Nasional Pariaman - Sumarni Sumarni; Refinaldi Refinaldi (Universitas Batanghari Jambi, 2020)
The purpose of this study, among others, is to analyze the effect of partially and simultaneously Internal Locus Of Control, Punichment Giving, and Visual Learning Style on Student Learning Achievement of STKIP Nasional Pariaman. The method used is quantitative research with the research design used associative research. The entire sample in this study was taken from the total population of class 2017 to 2019, so that the sample size was 33 students. The data analysis technique used in this study is multiple linear regression analysis. The results showed that the variables Internal Locus of Control, Punichment Giving and Visual Learning Style had a positive and partially significant effect on Student Learning Achievement. This can be seen from the level of significance of the t test conducted at p = 0.000 for the Internal Locus of Control variable, p = 0.004 for the Punichment Giving variable, and p = 0.009 for the Visual Learning Style variable. Each of these independent variables has a p value <0.05. So it can be said that ho is rejected and Ha is accepted. Simultaneously the Internal Locus Of Control variable, Punichment Giving and Visual Learning Style have a positive and significant effect on Student Learning Achievement. This can be seen from the level of significance of the F test which was carried out at 0.000 <0.05.